God's Inclusive House? Narrating the Views of Religious Figures on Accessibility and Services for Houses of Worship in the Banjar Community - Ramadan, Willy; Amin, Barkatullah (Indonesian Journal of Disability Studies, 2023)
This article will discuss how the accessibility of places of worship for persons with disabilities in the Banjar community and also the views of religious leaders regarding these services and accessibility. The research method used is qualitative with a phenomenological approach. The interviews were chosen data collection techniques with 5 religious’ leaders with a purposive sampling technique as the subject. The results of this study found that the house of worship in the Banjar community in South Kalimantan was still not referred to as an accessible congregation. This means that places of worship for religions in South Kalimantan, both physically, in communication, and in attitudes, cannot be easily accessed by persons with disabilities. However, even so, indicators of community displayed by all religions are already open and friendly to people with disabilities. This is evidenced by the forms of religious services provided by the church management or people with disabilities. The second finding explains that the views of religious leaders show great and positive concern for people with disabilities in South Kalimantan. In general, the views of religious people can be categorized into 3 major views: (1) The existence of a house of worship that is designated with non-Muslims, which is appointed by the Regional Government, as a house of worship that has complete facilities for persons with disabilities; (2) The house of worship has a special room for persons with disabilities; (3) Disability-friendly houses of worship are the focus of religious services.